Evaluation of [(13)N]ammonia positron emission tomography as a potential method for quantifying glutamine synthetase activity in the human brain - Egerton, Alice (EJNMMI Res, 2020)
PURPOSE: The conversion of synaptic glutamate to glutamine in astrocytes by glutamine synthetase (GS) is critical to maintaining healthy brain activity and may be disrupted in several brain disorders. As the GS catalysed conversion of glutamate to glutamine requires ammonia, we evaluated whether [(13)N]ammonia positron emission tomography (PET) could reliability quantify GS activity in humans. METHODS: In this test–retest study, eight healthy volunteers each received two dynamic [(13)N]ammonia PET scans on the morning and afternoon of the same day. Each [(13)N]ammonia scan was preceded by a [(15)O]water PET scan to account for effects of cerebral blood flow (CBF). RESULTS: Concentrations of radioactive metabolites in arterial blood were available for both sessions in five of the eight subjects. Our results demonstrated that kinetic modelling was unable to reliably distinguish estimates of the kinetic rate constant k(3) (related to GS activity) from K(1) (related to [(13)N]ammonia brain uptake), and indicated a non-negligible back-flux of [(13)N] to blood (k(2)). Model selection favoured a reversible one-tissue compartmental model, and [(13)N]ammonia K(1) correlated reliably (r(2) = 0.72–0.92) with [(15)O]water CBF. CONCLUSION: The [(13)N]ammonia PET method was unable to reliably estimate GS activity in the human brain but may provide an alternative index of CBF.